Wind–wave coupling effect on the dynamic response of a combined wind–wave energy converter - Li, Jinghui; Shi, Wei; Zhang, Lixian; Michailides, Constantine; Li, Xin (My University, 2021)
There is a huge energy demand from offshore renewable energy resources. To maximize the use of various renewable energy sources, a COMBINED floating energy system consisting of different types of energy devices is an ideal option to reduce the levelized cost of energy (LCOE) by sharing the infrastructure of the platform and enhancing the power production capacity. This study proposed a combined concept of energy systems by combing a heave-type wave energy converter (WEC) with a semisubmersible floating wind turbine. In order to investigate the power performance and dynamic response of the combined concept, coupled aero-hydro-servo-elastic analysis was carried out using the open-source code F2A, which is based on the coupling of the FAST and AQWA tools by integrating all the possible environmental loadings (e.g., aerodynamic, hydrodynamic). Numerical results obtained by AQWA are used to verify the accuracy of the coupled model in F2A in predicting dynamic responses of the combined system. The main hydrodynamic characteristics of the combined system under typical operational conditions were examined, and the calculated responses (motions, mooring line tension and produced wave power) are discussed. Additionally, the effect of aerodynamic damping on the dynamic response of the combined system was examined and presented. Moreover, a second fully coupled analysis model was developed, and its response predictions were compared with the predictions of the model developed with F2A in order for the differences of the calculated responses resulted by the different modeling techniques to be discussed and explained. Finally, the survivability of the combined concept has been examined for different possible proposed survival modes.
Keywords: Wind–wave energy structures; Wind turbine; Fully coupled analysis; Hydrodynamic response; Aerodynamic damping; Wave energy converters